PENGUATAN PENGAWASAN AKUNTABILITAS KINERJA APARATUR SIPIL NEGARA (ASN) BERBASIS WHOLE OF GOVERMENT APPROACH DALAM PERSPEKTIF DYNAMIC GOVERNANCE - Jihan Nabilatul Azzah; Arif Hidayat (Universitas Bojonegoro, 2025)
This study aims to identify and analyze the strengthening of accountability supervision of Civil Servants (ASN) performance using the Whole of Government (WOG) approach in the perspective of Dynamic Governance. The method used is a normative juridical approach, with library research techniques to gather data from laws, government policies, and related literature. This study analyzes the legal provisions governing the merit system and ASN accountability in the context of applicable regulations, and evaluates the implementation of performance supervision of ASN based on WOG and Dynamic Governance. The research findings show that despite clear legal foundations, the implementation of the merit system emphasizing accountability in Indonesia still faces significant challenges, such as the lack of coordination between agencies, political interference, and suboptimal use of information technology. Moreover, the implementation of WOG involving collaboration between government agencies should be promoted to create more integrated and efficient supervision. The Dynamic Governance perspective offers a solution by introducing adaptation and flexibility in the supervision system to address rapid social, economic, and technological changes. This study suggests reforms in the ASN supervision system to make it more transparent, accountable, and responsive to ongoing developments.